"DRAWS": an application for small-scale electronic draws - Charitos, Nicolaos; Papaioannou, Evi (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
We present "Draws", an application for conducting small-scale draws. The efficiency of the procedure and the true random and unbiased nature of the computed results stems from the theoretical soundness of the exploited shuffling algorithms, namely Durstenfeld-Knuth shuffle and its predecessor, Fisher-Yates shuffle. Using the application does not require advanced computer skills or sophisticated equipment. The application could highly facilitate and enhance administrative procedures offering speed and transparency.